2018
DOI: 10.1146/annurev-orgpsych-032117-104640
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Resources in the Organizational Context: The Reality of Resources and Their Consequences

Abstract: Click here to view this article's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

354
5,406
15
60

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,159 publications
(5,835 citation statements)
references
References 154 publications
354
5,406
15
60
Order By: Relevance
“…As prior studies have suggested (e.g., Sherony & Green, ) and our current research shows as well (i.e., the negative relationship between workplace ostracism and LMX), positive co‐worker relations and a high‐quality LMX tend to be found together. In the language of COR theory, the LMX and co‐worker relations are closely linked and thus travel in caravans (Hobfoll et al, ). With that pattern in mind, we speculate that, if an employee suffers ostracism despite his or her high‐quality LMX, managing that mistreatment may be beyond his or her ability (Halbesleben et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As prior studies have suggested (e.g., Sherony & Green, ) and our current research shows as well (i.e., the negative relationship between workplace ostracism and LMX), positive co‐worker relations and a high‐quality LMX tend to be found together. In the language of COR theory, the LMX and co‐worker relations are closely linked and thus travel in caravans (Hobfoll et al, ). With that pattern in mind, we speculate that, if an employee suffers ostracism despite his or her high‐quality LMX, managing that mistreatment may be beyond his or her ability (Halbesleben et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two such resources i.e. resilience and perceived supervisor support have been established as intrapersonal and extra‐personal resources, respectively, that protects employees against the harmful effects of workplace stressors (Hobfoll, Halbesleben, Neveu, & Westman, ). In line with this theory, we believe that nurses resilience trait act as a personal coping resource and their perceptions of supervisor support as social resource that helps protect them from engaging in deviant behaviors when exposed to incidences of workplace bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current study employs the conservation of resource (COR) theory to explore the consequences of workplace ostracism (Hobfoll, Freedy, Lane, & Geller, ; Hobfoll, Halbesleben, Neveu, & Westman, ). One of the major advantages of applying COR theory is the ability to observe multiple potential factors affecting the relationship between perceived workplace ostracism and subsequent outcomes.…”
Section: Introductionmentioning
confidence: 99%